Trap Culture and Colonization of Arbuscular Mycorrhizal Fungi from Corn Roots in Tidal Swamps Using Several Host Plants - Marlin Sefrila; Munif Ghulamahdi; Purwono Purwono; Maya Melati; Irdika Mansur (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Arbuscular mycorrhizal fungi (AMF) are mycorrhizal from the endomycorrhizal group. The fungi live on higher plants' roots by performing symbiotic mutualism. This study aimed to identify AMF spores after trapping in corn roots and the degree of root infection by AMF in several host plants. The study was conducted using tidal swamps soil samples taken from Mulyasari Tanjung Lago Village, Banyuasin Regency, South Sumatra. The experiment used a randomized block design and three replicates with four host plants as a treatment: corn, soybean, sugarcane (monoculture) and sugarcane-soybean (combination). The results showed that AMF spores found on corn roots after trapping were from the Acaulospora sp. and Glomus sp. groups. Hyphae, vesicles, arbuscules and spores are AMF structures found in the roots of host plants infected by AMF. The percentage of AMF infection in host plant roots ranged from 1.11% to 77.44% where the highest was in maize host plant roots at 77.44% in the form of internal hyphae. The maize host plant has a high potential to be colonized by AMF compared to a mixture of soybean, sugarcane and sugarcane-soybean.